A LIFE-EXHAUSTION: INTERRELATION WITH THE PREVALENCE OF ISCHEMIC HEART DISEASE - M. M. Kayumova; E. V. Akimova; V. V. Gafarov; R. Kh. Kayumov; A. M. Akimov; V. A. Kuznetsov (Российский кардиологический журнал, 2014)
Aim. To findout the interrelation of ischemic heart disease prevalence and higher level of life exhaustion in the open population of men 25-64 y.o. in the average- urbanized Siberian city.Material and methods. Simultaneous epidemiological study was performed on representative group, made up from the lists of citizens in one of Tyumen districts, consisting of 1000 men, 250 by every decade of lifetime (25-34, 35-44, 45-54, 55-64 y.o.). The respond rate reached 85% — 850 participants. The levels of life exhaustion were assessed by the WHO algorithm MONICA — psychosocial, and the prevalence of CHD — by common epidemiological criteria. Results. More than in the half of men 25-64 y.o. in Tyumen the life-exhaustion was revealed (standard value 54,5%). Higher level of LE in population was 15,9%. In open population of 25-64 y.o. men the odds ratio for the absence/presence of CHD was 6,02; definite form of CHD — 14,11; probable type of CHD with higher LE did not show significance.Conclusion. The data witnesses the possibility of further studying of psychosocial risk factors in men of economic-active age in Siberian populations and the importance of preventive activities to reduce the influence of psychosocial risk factors.